Zakat sebagai Instrumen Solidaritas Sosial Analisis Sosiologis terhadap Mekanisme dan Tantanganya - Fandi Y. Irawan; Syamsurizal Yazid (Al-Tasyree: Jurnal Bisnis, Keuangan dan Ekonomi Syariah, 2025)
Zakat is a socio-religious instrument that plays a strategic role in structuring distributive justice in society. This study aims to analyze the mechanism of zakat in constructing social solidarity and to map its contemporary challenges through a sociological perspective. Utilizing a library research method with content analysis, this study examines Yusuf al-Qardhawi's Fiqh az-Zakat framework using the theoretical lenses of Émile Durkheim, Marcel Mauss, and Pierre Bourdieu. The results indicate that zakat functions as a driver of organic solidarity through a pattern of functional interdependence between social classes. Based on Mauss's theory, zakat generates symbolic reciprocity in the form of communal stability. Meanwhile, in Bourdieu’s view, productive zakat acts as a vehicle for converting economic capital into cultural and social capital to eradicate marginalization. However, the effectiveness of zakat as a social technology faces severe challenges, including psychological distance caused by impersonal digitalization, issues of public trust in modern institutionalization (BAZNAS/LAZ), and low zakat awareness driven by individualism and materialism. This study concludes that the future success of zakat relies heavily on the synergy between socio-religious literacy enhancement, institutional professionalism, and humanistic technological adaptation